2015
DOI: 10.1590/0004-282x20140144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of group psychotherapy on cognitive function in patients with multiple sclerosis with cognitive dysfunction and depression

Abstract: Avaliação do efeito da psicoterapia de grupo sobre as funções cognitivas de pacientes com esclerose múltipla que apresentam simultaneamente alterações cognitivas e depressão Multiple sclerosis (MS) is a chronic inflammatory disease considered to be of autoimmune origin and characterized by focal inflammatory-demyelinating lesions, neuroinflammation, and neurodegeneration of the central nervous system (CNS), affecting the white matter, cortex and deep gray matter of the brain 1 . The demyelination associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A study conducted on MS patients with various degrees of depression revealed greater neuropsychological dysfunction, as compared to non-depressed MS patients (34). Moreover, psychotherapy has been suggested as a method of decreasing cognitive impairments in MS patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on MS patients with various degrees of depression revealed greater neuropsychological dysfunction, as compared to non-depressed MS patients (34). Moreover, psychotherapy has been suggested as a method of decreasing cognitive impairments in MS patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Health comorbidities were explicitly mentioned in the form of cognitive dysfunction (i.e., impaired memory, attention, executive function, etc. ; Bilgi et al, 2015; Guest et al, 2015; Hanssen et al, 2016; Pakenham et al, 2018), traumatic brain injury (Craig et al, 2017; Guest et al, 2015), and unspecified conditions (Anderson et al, 2017; Navarta-Sánchez et al, 2020). Other comorbidities included chronic illness (Canivet et al, 2016), as well as “psychiatric diagnosis” (Berardelli et al, 2018) and “serious illness” (Fitzpatrick et al, 2010) as being present among participants with physical disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 55 studies, 17 studies incorporated components of homework given to participants. Most of these included practicing exercises and skills learned during psychosocial group therapy sessions (Hadinia et al, 2017), such as relaxation exercises (Graziano et al, 2014), mindfulness practice (Advocat et al, 2016), self-guided homework (Anderson et al, 2017), and cognitive exercises (Bilgi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations